An Immunohistological Study of Human and Murine Lymphomata. - Taylor, C (1974)
The pathology of the lymphomas poses two major problems, quite apart from the clinical aspects of therapy. The first problem relates to diagnosis and classification, and stems from the continuing lack of a clear understanding of the basic cell types from which these neoplasms take origin. The second problem concerns the nature of the pathological process and its causation. The aetiological factors which have been considered in relation to the lymphoid neoplasms are those of neoplasia in general. In addition, there are a number of reports in human and animal pathology where a lymph node subjected to prolonged immunological stimulation develops a progressive hyperplasia, which terminates as a frank malignant neoplasm of one of the component cells of the lympho- reticular system. This thesis is concerned with both of these aspects and is presented in four consecutive parts. Part I In Part I the functional anatomy of the lympho-reticular system is reviewed and the morphology of the lymph node is considered in relation to normal immune responses. The individual reacting cells are defined morphologically and their functional and developmental inter-relations are examined Current classifications of human and murine lymphoid neoplasms are discussed and the usage of the term 'reticulum cell' is examined. The European concept of lymphomata distinguishes three principal types of lympho-reticular reactions, in accordance with the descriptions of Robb-Smith (1936, 1938, 1947, 1964). These have been summarised by Lennert (1966): Reactive hyperplasia Sarcomas of lympho-reticular tissue 'a group of lymph node disease lying between the reactive hyperplasia and the sarcomas': Autonomous hyerplasia (Lennert) Progressive hyperplasia, Reticulosis (Robb-Smith). Further classification is then based upon the presumption that, any of the individual component cells of the lympho-reticular system may display any of these three types of reactions - hyperplasia - progressive hyerplasia - sarcoma. The application of this system of nomenclature produces a precise, but lengthy, classification as given by Robb-Smith (1964) from which certain named conditions may be selected: Follicular lymphoma and lymphosarcoma Reticulum cell sarcoma Hodgkin's disease. These conditions are equivalent to the less intricate American concept of the malignant lymphomas. The principal types of malignant lymphoma have been summarised by Lukes (1966): Lymphocytic lymphoma Stem cell lymphoma Histiocytic lymphoma Hodgkin's disease. (each may occur in a nodular or diffuse form). One of the principal problems is thus illustrated. This is the definition of the 'reticulum cell', and the neoplasms which are presumed to be derived from it. The term reticulum cell sarcoma is represented in the American literature by a combination of stem cell lymphoma and histiocytic lymphoma. This problem may be clarified by recognising the schizoid nature of the 'reticulum cell'. A study of the literature supports the view that the term reticulum cell has been used to represent two principal cell types: 'Reticulum cell' Histiocytic series       Transformed lymphocytes This proposition is supported by the evidence presented in Parts II and III of this thesis. Part II In Part I some of the morphological criteria for identification of lympho-reticular cells were examined, and found wanting in some respects, particularly with reference to the radial cytological changes occurring during the life cycle of the lymphocyte. For this reason an investigation was made of the various techniques which might serve to supplement orthodox morphological criteria in the identification of cells of the lymphocyte series. In Chapter V the use of immunofluorescence techniques with anti-lymphocyte and anti-thymocyte sera was explored as a possible means of specifically labelling lymphoid cells. Some surprising results were obtained in that myeloid cells of foetal tissues showed intense fluorescence, while lymphocytes showed a lesser degree of fluorescent staining. The method did not appear to be directly applicable to the study of lymphomatous tissues. Chapter VI is concerned with the intrinsic disadvantages of immunofluorescence techniques, principally the requirement for fresh or specially processed tissues and the poor cellular morphology inherent in the method. An immunoperoxidase technique was developed (Taylor and Burns, 1974; Burns, Hambridge and Taylor, 1974) which allows the demonstration of immunoglobulin in formalin-fixed paraffin embedded material, and results in good morphological detail. This method, which depends upon the demonstration of antigenic determinants upon immunoglobulin molecules by a peroxidase conjugated antibody, was applied to a study of reactive hyperplasia and to some of the lympho-reticular neoplasms of man. In such preparations it was possible to identify individual cells according to accepted morphological criteria, with the added advantage that some lymphoid cells were identifiable independently by their content of immunoglobulin. The specificity and sensitivity of this immunoperoxidase method was compared to that of established immunofluorescence techniques under several different conditions of tissue processing. The specificity of the method was found to be at least equivalent to that of fluorescence methods, and there was a slight reduction in sensitivity detectable in frozen tissues only. The specificity of the immunoperoxidase method was further confirmed by a study of tissue from cases of myelomatosis, in which the class of paraprotein was determined independently. In this study there was some evidence of the lymphoid nature of at least some so called 'reticulum cells'. Several cases of multiple myeloma progressing to plasma cell reticulo-sarcoma were examined (Taylor and Mason, 1974). Monoclonal immunoglobulin was demonstrated within the cells of these poorly differentiated sarcomas which were indistinguishable on purely morphological grounds from other lesions classified as reticulum cell sarcoma (and showing no clinical evidence of paraprotein production). Finally some refinements of the basic peroxidase conjugated antibody procedure were devised. As a result the method employing immune complexes of horseradish peroxidase antigen with rabbit antibody to horseradish peroxidase (PAP method) as the final stage of a sandwich method (Diag. 18. p. 214) was adopted for all subsequent studies of human and murine tissues. The application of the PAP method for demonstrating intracellular immunoglobulin to lymphomas including Hodgkin's disease is described in Chapters VII and VIII. Intracellular immunoglobulin was observed in the neoplastic cells of cases of follicular lymphoma and 'reticulum cell sarcoma', including forms which might otherwise be classified as 'stem cell' or 'histiocytic' lymphomas. In some cases the pattern of immunoglobulin staining was clearly monoclonal (exclusively kappa chain or exclusively lambda chain within the neoplastic population) but in others both kappa and lambda chain were apparently present in the same cell. This latter pattern of immunoglobulin staining was also observed in some of the Reed-Sternberg and atypical mononuclear cells of Hodgkin's disease (Taylor, 1974). The possible significance of these results is considered in Chapter X where it is concluded that at least some of the 'malignant reticulum cells' of reticulum cell sarcoma and Hodgkin's disease are closely related to the transformed lymphocyte. This conclusion is considered in relation to the concepts of Lukes and colleagues of lymphomas derived from follicular centre cells, and the findings are summarised in Diag.19, p.317. In Chapter IX the use of antisera directed against muramidase was examined as a possible marker for cells of the histiocyte series, and some diffuse lymphomas were discovered which appeared to be of true histiocytic origin. Part III This part is concerned with the concepts of progressive hyperplasia with termination as frank malignant neoplasia of the lympho-reticular system ('reticulum cell' sarcoma of the mouse). The morphology of B & T cell immune responses of the 'normal' mouse was examined in detail, as a baseline for the subsequent assessment of the evolution of neoplasia (Chapter XI). Morphological features of mesenteric node and spleen were examined in three strains of mice characterised by a high incidence of spontaneous lymphoma: SJL/J (Chapter XII) NZB (Chapter XIII) PBA (Chapter XIV) In addition the phases of development of lymphoma arising in the course of 'chronic allogeneic disease' were studied in (BALB/C x A/J)F1 hybrid mice given injections of parental (BALB/C) spleen cells at six weeks of age (Chapter XV). Small groups of mice of each strain were autopsied at regular intervals irrespective of evidence of clinical disease, and the morphological changes occurring in mesenteric node and spleen were assessed with reference to the normal patterns of B & T cell immune responses. Standard morphological criteria were employed in all mice, and tissues from selected animals were further examined by certain histochemical methods and by the PAP method for demonstrating intracellular immunoglobulin. Certain similarities were observed in each of the four strains examined, and three phases of lympho-reticular response were distinguished: Simple hyperplasia Atypical hyperplasia Malignant neoplasia (reticulum cell sarcoma). In each case it was concluded that the malignant 'reticulum cell' was derived from the transformed B lymphocyte of the reactive follicle during the course of sustained follicular hyerplasia. Part IV In Part IV the various observations reported in Parts II and III of immunoglobulin containing cells in reactive hyperplasia and lympho-reticular neoplasia in man and mouse are correlated and integrated within the current concepts of function of the lympho-reticular system as described in Part I. Explanations are thereby offered for some of the remaining enigmas in the pathology of lympho-reticular neoplasms. Firstly the reticulum cell is recognised for what it is - a composite of several distinct cell types, in particular the histiocyte and the morphological forms of the transformed lymphocyte. Secondly, admitting the possibility that some neoplasms of 'reticulum cells' are in fact neoplastic derivatives of the transformed lymphocyte, these and the obvious lymphocytic lymphomas are examined for evidence of a T or B cell origin. Thirdly, the role of a prolonged immune reaction in the induction of lympho-reticular neoplasia is considered, and the logical sequence, of B cell hyperplasia with plasmacytosis evolving through a process of sustained lymphocyte transformation to a neoplasma derived from the transformed B cell, is explored. Then the pathogenesis of Hodgkin's disease is re-examined in accordance with the proposed view that Hodgkin cells and Reed-Sternberg cells are abnormally transformed (neoplastic) B lymphocytes and a possible explanation is offered for the mixed cellular picture characteristic of Hodgkin's disease. Finally the various lymphomata are compared to the sequence of morphological changes occurring during transformation of the B lymphocyte (summarised in Diag. 19. p.317) and are also inter- related one to another through the lymphocyte cell cycle during transformation (Diag. 38. p. 509).